Úloha municipalit v otázce ochrany týraných a opuštěných zvířat - Brychtová, Šárka (Univerzita Pardubice, 2009)
The article is framed into two main levels. In the first part of the subscription – it deals with philosophical problem of animal rights and their protection with outline of natural and science conception and last research of animal intelligence. It takes in brief excursion this problematic in historical development of legislature and public opinion. The second part runs problematic of dogs shelters (asylums) in relation to public service, local government and the whole of society. It takes in especially situation after 1989. It made much in this problematic and animal rights are perhaps well treated, but praxes is different off course and it depends on representatives of municipalities how are able to fill valid regulations and their financial possibilities. Closing part mentions also briefly condition of this problematic in time of economic crisis and its impact to shelters.
Keywords: animal rights; animal protection; dogs asylums; municipal dogs asylums